2010
DOI: 10.1186/1471-2296-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of stroke risk factors among primary care patients with previous stroke or TIA: a questionnaire study

Abstract: BackgroundSurvivers of stroke or transient ischaemic attacks (TIA) are at risk of new vascular events. Our objective was to study primary health care patients with stroke/TIA regarding their knowledge about risk factors for having a new event of stroke/TIA, possible associations between patient characteristics and patients' knowledge about risk factors, and patients' knowledge about their preventive treatment for stroke/TIA.MethodsA questionnaire was distributed to 240 patients with stroke/TIA diagnoses, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
4
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 25 publications
(36 reference statements)
10
37
4
3
Order By: Relevance
“…Eleven studies reported data related to stroke risk factor knowledge among stroke survivors. The most encouraging of these was conducted by Sloma et al [8 ]who found that, when asked ‘How do you think that (risk factor) influences the risk of having a new stroke or TIA? ', approximately 90% of stroke survivors knew that hypertension, hyperlipidemia and smoking increase an individual's risk of stroke.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies reported data related to stroke risk factor knowledge among stroke survivors. The most encouraging of these was conducted by Sloma et al [8 ]who found that, when asked ‘How do you think that (risk factor) influences the risk of having a new stroke or TIA? ', approximately 90% of stroke survivors knew that hypertension, hyperlipidemia and smoking increase an individual's risk of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…They should: (1) be structured and continue over an extended period of time, (2) occur at each stage/level of engagement within the healthcare system, (3) include different delivery formats (e.g. 1-to-1 or a group), (4) emphasize all modifiable risk factors and (5) include information about belief systems [8,30,48,60,61,62,63]. Finally, great care should be taken to ensure that standard information is provided in a uniform and consistent manner across settings and practitioners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AH, hyperlipidemia and tobacco smoking are identified as risk factors of new vascular events by nearly 90% of 182 surviving primary care patients with previous IS or TIA while AF and diabetes mellitus are recognized by less than 50% of these patients (43).…”
Section: Risk Factors and Prognosismentioning
confidence: 99%
“…İskemik inme veya TİA öyküsü olan hastalarda tekrar inme geçirme riskinin arttığı bilinmektedir (16). Bizim çalışmamızda da geçirilmiş SVH öyküsü; hasta grubunda % 39.2, kontrol grubunda % 5 oranında olup istatiksel olarak anlamlı olarak bulundu (p<0.001).…”
unclassified